Emerging methods in wound care: an update - Vagholkar, Ketan; Vaghani, Akshaykumar (International Surgery Journal, 2026)
Chronic wounds [diabetic foot ulcers (DFUs), venous leg ulcers (VLUs), pressure injuries] and complex acute wounds impose substantial morbidity, reduced quality of life and high health-care costs. Many wounds fail to heal because of impaired angiogenesis, persistent inflammation, hypoxia, senescent cells, dysfunctional extracellular matrix (ECM) and biofilm-laden microbiomes. Recent innovations target these pathophysiologic drivers. This narrative review synthesizes contemporary advances in wound care across biologic or regenerative therapies, advanced biomaterials, antimicrobial or anti-biofilm strategies, device-based physical modalities, smart dressings, digital integration and 3D printing or bioprinting. The mechanisms, representative technologies, clinical indications, evidence strength, practical considerations and safety or regulatory challenges are summarized. Biologic approaches include cellular therapies [autologous or allogeneic keratinocytes, fibroblasts, mesenchymal stromal or stem cells (MSCs)], platelet-derived products, engineered skin substitutes and emerging gene or RNA therapies offering targeted modulation of inflammation, angiogenesis and matrix repair. However, they all require rigorous wound bed preparation and patient optimization. Advanced dressings (hydrogels, protease-modulating matrices, electrospun scaffolds, antimicrobial-integrated and oxygen-releasing materials) improve local milieu and enable controlled therapeutic delivery. Antimicrobial strategies addressing biofilms include enzymatic dispersal agents, bacteriophage therapy and local antibiotic delivery systems. However, multimodal use with debridement is superior to single interventions. Device-based modalities [Negative pressure wound therapy (NPWT) and NPWTi, electrical stimulation (ES), photobiomodulation, photodynamic therapy (PDT), oxygen therapies, ultrasound or shockwave] show utility in specific contexts with strongest evidence for NPWT. Smart sensors, closed-loop dressings and AI-enabled digital assessment promise earlier detection and personalized interventions but need outcome validation. 3D printing and bioprinting enable patient-specific scaffolds and tissue constructs but face vascularization and regulatory barriers. Multimodal, evidence-guided, patient-personalized approaches built on optimized systemic care and meticulous wound bed preparation are most likely to improve outcomes. Key needs include standardized endpoints, larger pragmatic trials, cost-effectiveness data and implementation frameworks to ensure safety, regulatory compliance and equitable access.